Dynamic Effects on the Stability of International Environmental Agreements - Aart de Zeeuw (Fondazione Eni Enrico Mattei (FEEM), 2005)
In terms of the number of signatories, one observes both large and small international environmental agreements. The theoretical literature, based on game theory, discusses different concepts and mechanisms for the stability of coalitions and has reached the conclusion that, under farsightedness, both large and small stable coalitions can occur. In the context of a repeated game, this implies that large stable coalitions can also be sustained over time by a simple trigger mechanism, for large enough discount factors. However, if changes in time implement changes in state, this conclusion does not hold anymore: only small stable coalitions can be sustained.
Keywords: Q2; C70; F42; 330; IEAs; Coalitional stability; Dynamics; Umweltabkommen; Wiederholte Spiele; Koalition; Theorie